Peran Kompetensi Tenaga Kefarmasian dalam Memediasi Pengaruh Etika Kerja dan Budaya Kerja terhadap Implementasi Medication Safety - Setia Dwi Wardhani; Sunarjo, Wenti Ayu (Universitas Pahlawan Tuanku Tambusai, 2025)
This study examines the influence of work ethics and work culture on the implementation of medication safety by the pharmacy personnel competence as a mediating variable. The subjects of the study involved pharmaceutical personnel, namely 17 pharmacists and 19 pharmacy vocational personnel, with a total of 36 respondents. The study used a quantitative approach with data collection through a Likert scale-based questionnaire, which was then processed using SmartPLS 4. The results of the study concluded that work ethics had a significant positive effect on the implementation of medication safety, work culture had a positive but insignificant impact on the implementation of medication safety, pharmaceutical personnel competence had a positive but insignificant effect on the implementation of medication safety, work ethics had a significant positive impact on the pharmacy personnel competence, work culture had a positive but insignificant effect on the pharmacy personnel competence, work ethics did not directly affect the implementation of medication safety with the mediation of pharmaceutical personnel competence, work culture did not directly affect the implementation of medication safety with the mediation of pharmaceutical personnel competence. Keywords: Work ethics, Work culture, Pharmacy personnel competence, Medication Safety